Poria cum Radix Pini Rescues Barium Chloride-Induced Arrhythmia by Regulating the cGMP-PKG Signalling Pathway Involving ADORA1 in Zebrafish - Yang, Ning-Juan; Liu, Yan-Ru; Tang, Zhi-Shu; Duan, Jin-Ao; Yan, Ya-Feng; Song, Zhong-Xing; Wang, Ming-Geng; Zhang, Yu-Ru; Chang, Bai-Jin; Zhao, Meng-Li; Zhao, Yan-Ting (Frontiers in Pharmacology, 2021)
The traditional Chinese medicine Poria cum Radix Pini (PRP) is a fungal medicinal material that has been proven to play an important role in the treatment of arrhythmia. However, the mechanism of its effect on arrhythmia is still unclear. In this study, network pharmacology and metabolomics correlation analysis methods were used to determine the key targets, metabolites and potential pathways involved in the effects of PRP on arrhythmia. The results showed that PRP can significantly improve cardiac congestion, shorten the SV-BA interval and reduce the apoptosis of myocardial cells induced by barium chloride in zebrafish. By upregulating the expression of the ADORA1 protein and the levels of adenosine and cGMP metabolites in the cGMP-PKG signalling pathway, PRP can participate in ameliorating arrhythmia. Therefore, we believe that PRP shows great potential for the treatment of arrhythmia.